65 OBESITY, DIABETES, AND INSULIN RESISTANCE: RELATION TO ELEVATED C-REACTIVE PROTEIN LEVELS IN AFRICAN AMERICANS. Issue 1 (1st January 2007) - Taylor, J. K.; Taylor, H. A.; Benjamin, E. J.; Rotimi, C. N.; Sarpong, D. F.; Wilson, J. G.; Samdarshi, T.; Steffes, M. W.; Fox, E. R.
Abstract : Purpose: Elevated C-reactive protein (CRP) has been strongly related to obesity, diabetes (DM), and insulin resistance (IR) in predominantly white non-Hispanic cohorts. There is limited information on systemic inflammation in African Americans. Methods: The study cohort consisted of 5, 202 participants (55 ± 13 years, 64% female) who presented for Jackson Heart Study Exam 1 (2001-2004). The contribution of traditional risk factors to the variability of CRP was tested using a stepwise regression model. We evaluated the relation of obesity, DM and IR to CRP among participants using analysis of variance. Results: In the stepwise regression, the amount of variability in CRP explained by clinical covariates was 23%. BMI explained 57% of the variability of CRP due to traditional risk factors. The mean CRP for participants was 1.4 mg/L for those nonobese without IR, 3.2 mg/L for those obese without IR, 2.2 mg/L for those nonobese with IR, 4.0 mg/L for those obese with IR, 1.9 mg/L for those nonobese with DM, and 4.1 mg/L for those obese with DM. CRP was significantly higher for obese participants compared with nonobese participants regardless of IR or DM status ( p < .0001). For both obese and nonobese participants, CRP was significantly higher in nondiabetics with IR compared with nondiabetics without IR ( p < .0001). CRP was significantly higher in diabetics compared with nondiabetics without IR ( p < .0001). Conclusions: In this large population-based cohort of African Americans, we found that among traditional risk factors, BMI contributed the greatest to the variability of CRP. DM and IR were also significantly related to CRP.